Comparative study of the political view of Abdur-Rahman Al-Kawakibi and Shakib Arsalan - Shuriye, Abdi Omar; Ajala, Mosud T. (Mediterranean Center of Social and Educational Research, 2014)
Both al-Kawakibi and Arsalan lived in late nineteenth century characterised with decline of the Muslim nations and the British, French and Italian imperialism. Muslims became promoters of the imperialist cause and Muslim elites were separating religion from politics an idea en route to secularism. The state of Muslims during this period was same everywhere, though varies in degree. Muslims lag far behind in almost everything. Al-Kawakibi and Arsalan rose to identify the causes of the decline of the Muslim ummah as majorly an internal factor than external. Similarly they promoted the return to Al-Qur’an and fundamental principles of Islam, and further advocated Knowledge for all, without dichotomy between religion and science.